Necessity of Sleep for Motor Gist Learning in Mice - Pettibone, Ward D.; Kam, Korey; Chen, Rebecca K.; Varga, Andrew W. (Frontiers in Neuroscience, 2019)
With respect to behavior, the term memory “consolidation” has canonically been used to describe increased fidelity during testing to a learned behavior shaped during training. While the sleeping brain appears to certainly aid in consolidation by this definition for a variety of memories, including motor memories, growing evidence suggests that sleep allows for much more flexible use of the information encountered during prior wakefulness. Sleep has been shown to augment the extraction of gist or patterns from wake experience in human subjects, but this has been difficult to recapitulate in animal models owing to the semantic requirements in many such tasks. Here we establish a model of motor gist learning in mice in which two bouts of exclusive forward running on the rotarod significantly augments the first experience of exclusive backward running. This augmentation does not occur if sleep is disrupted following the forward running template behavior or if a period of natural wakefulness follows one of the two bouts of exclusive forward running. This suggests that sleep is required for the extraction of the motor gist of forward running to apply to backward running.